Comparative genomics enabled the isolation of the R3a late blight resistance gene in potato - Huang, S.; Van Der Vossen, E.A.G.; Kuang, H.; Vleeshouwers, V.G.Aa; Zhang, N.; Borm, T.J.A.; Van Eck, H.J.; Van Eck, H.J.; Jacobsen, E.; Visser, R.G.F.
Comparative genomics provides a tool to utilize the exponentially increasing sequence information from model plants to clone agronomically important genes from less studied crop species. Plant disease resistance (R)loci frequently lack synteny between related species of cereals and crucifers but appear to be positionally well conserved in the Solanaceae. In this report, we adopted a local RGA approach using genomic information from the model Solanaceous plant tomato to isolate R3a, a potato gene that confers race-specific resistance to the late blight pathogen Phytophthora infestans. R3a is a member of the R3 complex locus on chromosome 11. Comparative analyses of the R3 complex locus with the corresponding I2 complex locus in tomato suggest that this is an ancient locus involved in plant innate immunity against oomycete and fungal pathogens. However, the R3 complex locus has evolved after divergence from tomato and the locus has experienced a significant expansion in potato without disruption of the flanking colinearity. This expansion has resulted in an increase in the number of R genes and in functional diversification, which has probably been driven by the o-evolutionary history between P. infestans and its host potato. Constitutive expression was observed for the R3a gene, as well as some of its paralogues whose functions remain unknown.
Keywords: R3A; COMPARATIVE GENOMICS; POTATO; TOMATO; DISEASE RESISTANCE; PHYTOPHTHORA INFESTANS